A knowledge-based expert system for aircraft gate assignment - So, Charles Tim Wing. (2009)
Assigning gates to incoming aircraft is an important activity at an airport, especially at a hub airport where the number of flights normally exhaust the number of available gates. A sensible allocation will optimise certain operational characteristics, such as reducing passenger walking distances and equipment transfer time - thus improving operational efficiency in general. Due to the complexity of the various constraints, the large scale of optimisation, and the ill-defined nature of the gate assignment problem, it cannot be solved satisfactorily by using traditional operations research techniques. Intelligent technologies, such as expert systems, offer an ideal approach to tackle complex and ill-defined problems through the use of heuristic and search techniques. Therefore, more and more airport administrators are exploring into the use of expert systems to provide optimum solutions in this area. Since each airport has its own physical and operational constraints and characteristics, these systems normally can only be applied to a particular airport and as a result, proprietary in nature.